[OP.7D.01] SAFETY AND BLOOD PRESSURE EFFECTS OF SECOND- VERSUS FIRST-GENERATION SYSTEM FOR ADMINISTERING BAROREFLEX ACTIVATION THERAPY. (September 2016) - Wachter, R.; Halbach, M.; Bakris, G.; Bisognano, J.; Haller, H.; Beige, J.; Kroon, A.A.; Nadim, M.; Lovett, E.; Schafer, J.; de Leeuw, P.W.
Abstract : Objective: To compare safety and blood pressure (BP) reductions obtained with first- and second-generation systems for administering baroreflex activation therapy (BAT) in patients with resistant hypertension, as well as to verify that BP reductions with active BAT are distinguishable from placebo and Hawthorne effects observed with sham control. Design and method: Second-generation data were available from 30 patients implanted in a single-arm verification study. For comparison, datasets for two groups of 30 first-generation patients were generated by propensity-matching demographic characteristics with patients who participated in a randomized, controlled trial. These patients had been assigned to either 12 months of active BAT or 6 months of inactive BAT followed by 6 months of active BAT (sham control). Using these cohorts, safety and BP reductions were compared for the first- and second-generation BAT systems. Results: Propensity-matching produced baseline characteristics that were statistically indistinguishable between the second-generation and first-generation cohorts. BP reductions over 12 months were comparable between second-generation patients and first-generation patients assigned to active therapy. Average BP reduction for second-generation patients through 12 months was 25 ± 3 mmHg (mean ± SE, p < 0.001), with 47% of patients reaching a systolic BP < 140 mmHg. Relative to sham control, second-generation patients exhibited an additional BP reduction at 6 months of 20 ± 7 mmHg (p = 0.008), while results at 12 months were comparable. Safety of the second-generation system was superior in terms of procedure time, complications and pulse generator lifetime. Figure. No caption available. Conclusions: First- and second-generation BAT systems provide comparable BP reductions in matched populations. The treatment effect of the second-generation BAT system is significantly greater than the placebo/Hawthorne effect observed in sham controls. Second-generation system safety is improved by a minimally-invasive implant procedure and a longer lasting pulse generator.